2016
DOI: 10.5194/isprsarchives-xli-b4-149-2016
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Accuracy Assessment of 30-M Resolution Alos, Aster, and SRTM Global Dems Over Northeastern Mindanao, Philippines

Abstract: ABSTRACT:The ALOS World 3D -30m (AW3D30), ASTER Global DEM Version 2 (GDEM2), and SRTM-30m are Digital Elevation Models (DEMs) that have been made available to the general public free of charge. An important feature of these DEMs is their unprecedented horizontal resolution of 30-m and almost global coverage. The very recent release of these DEMs, particularly AW3D30 and SRTM30m, calls for opportunities for the conduct of localized assessment of the DEM's quality and accuracy to verify their suitability for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 20 publications
1
42
0
2
Order By: Relevance
“…Elevados valores de R², acima de 0,9, são amplamente encontrados na literatura, em estudos de calibração do MDE SRTM a partir dos dados de pontos de controle de alta precisão vertical (e.g., Gorokhovich & Voustianiouk, 2006;Medeiros et al, 2009;Forkuor & Maathuis, 2012;Athmania & Achour, 2012;Santillan & Makinano-Santillan, 2016 Figura 3). Investigando a estratificação dessa variação em classes de altura ortométrica, foi possível observar uma diminuição de ∆H do SRTM não calibrado para o SRTM calibrado, em quase todas as classes, exceto na classe de 120 a 130m.…”
Section: Avaliação E Calibração Do Mde Srtm Para a áRea Regionalunclassified
See 1 more Smart Citation
“…Elevados valores de R², acima de 0,9, são amplamente encontrados na literatura, em estudos de calibração do MDE SRTM a partir dos dados de pontos de controle de alta precisão vertical (e.g., Gorokhovich & Voustianiouk, 2006;Medeiros et al, 2009;Forkuor & Maathuis, 2012;Athmania & Achour, 2012;Santillan & Makinano-Santillan, 2016 Figura 3). Investigando a estratificação dessa variação em classes de altura ortométrica, foi possível observar uma diminuição de ∆H do SRTM não calibrado para o SRTM calibrado, em quase todas as classes, exceto na classe de 120 a 130m.…”
Section: Avaliação E Calibração Do Mde Srtm Para a áRea Regionalunclassified
“…Essa precisão é 2 vezes maior do que a divulgada Gorokhovich & Voustianiouk (2006), observaram em estudos realizados nos EUA e na Tailândia, que a precisão vertical do SRTM, eram de duas a quatro vezes maiores que os valores apresentados nas especificações originais deste produto para as regiões estudadas. Para o Nordeste de Mindanau (Filipinas), Santillan & Makinano-Santillan (2016) verificaram que o SRTM para a região possuía uma precisão melhor do que a informada nas especificações originais desse MDE. Eles encontraram uma média de ΔH= 6,21m e RMSE= 8,28m, enquanto que nas especificações a média de ΔH esperado era de 10m e RMSE de 16m.…”
Section: Avaliação E Calibração Do Mde Srtm Para a áRea Regionalunclassified
“…The validation work about AW3D30 is very limited. Santillan et al [27] conducted a vertical accuracy assessment about AW3D30, ASTER GDEM and SRTM 1 in the Philippines with GPS points. It is found that the AW3D30 has the smallest RMSE of 5.68 m.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the DEM sources incorporated in previous studies (Tan et al, 2015, Xu et al, 2016 and the current study, it is clear that the factor controlling the significance of DEM source versus resolution is the vertical accuracy of DEM. Although vertical accuracy of different DEM sources may vary based on the study location (Elkhrachy, 2017, Santillan & Makinano-Santillan, 2016, the overall accuracy could be used as a guidance. When the vertical accuracies of employed sources are more or less similar, such as ASTER and SRTM with vertical accuracy of 17 meters at the 95% confidence level (https://asterweb.jpl.nasa.gov/GDEM.ASP) and less than 16m at the 90% confidence level (https://www2.jpl.nasa.gov/srtm/statistics.html), respectively, DEM resolution may play a critical role.…”
Section: Demmentioning
confidence: 99%